Anti-plasmodial activity of engeletin isolated from Artocarpus scortechinii - Latip, J.; Ali, A.H.; Hassan, N.; Shukor, N.I.; Sidek, H.M.; Embi, N. (Penerbit Universiti Kebangsaan Malaysia, 2014)
Ethnomedicinal use of plants from the Artocarpus genus has been extensively documented to include treatment of inflammation and malarial fever. Anti-plasmodial effects of Artocarpus scortechinii (synonym A. elasticus) reported against P. falciparum 3D7 culture in erythrocytes remain to be validated in vivo. The present study involved re-evaluation of anti-plasmodial activity of ethanolic extract of A. scortechinii in vitro, assessment of the extract for chemo-suppressive effects in vivo, and fractionation and identification of bioactive compounds. The ethanolic extract of A. scortechinii displayed moderate inhibitory activity towards growth of P. falciparum 3D7 (IC50=14.4±8.1 μg/mL) with minimal toxicity effect in mammalian Chang liver cells (selectivity index, SI=13.9). Administration of 25, 50 and 100 mg/kg body weight extract into P. berghei-infected mice for four consecutive days resulted in dose-dependent chemo-suppression of 43.2, 74.8 and 78.4% respectively. Vacuum liquid chromatography fractions of the ethanolic extract exhibited moderate to good in vitro anti-plasmodial activities. Further fractionation using Sephadex Column Chromatography yielded engeletin identified by nuclear magnetic resonance spectroscopy and mass spectroscopy. Upon further testing the isolated engeletin was shown to display an IC50 of 33.1±1.3 μM against the 3D7 parasite strain (SI=3.5). Data from the present study is the first report on anti-plasmodial activity of engeletin and its isolation from Artocarpus scortechinii.